[ACCEPTED]-How to change the order of arguments?-haskell
If you feel like editing functions after 46 they're written, you really really should 45 read Conal Elliott's excellent blog post 44 semantic editor combinators
http://conal.net/blog/posts/semantic-editor-combinators
In fact, everyone should read it anyway. It's 43 a genuinely useful
method (which I'm abusing 42 here). Conal uses more constructs than just 41 result
and flip
to very flexible effect.
result :: (b -> b') -> ((a -> b) -> (a -> b'))
result = (.)
Suppose I 40 have a function that uses 3 arguments
use3 :: Char -> Double -> Int -> String
use3 c d i = c: show (d^i)
and 39 I'd like to swap the first two, I'd just 38 use flip use3
as you say,
but if I wanted to swap 37 the seconnd and third, what I want is to 36 apply flip
to the result of applying use3
to its 35 first argument.
use3' :: Char -> Int -> Double -> String
use3' = (result) flip use3
Let's move along and swap 34 the fourth and fifth arguments of a function 33 use5
that uses 5.
use5 :: Char -> Double -> Int -> (Int,Char) -> String -> String
use5' :: Char -> Double -> Int -> String -> (Int,Char) -> String
use5 c d i (n,c') s = c : show (d ^ i) ++ replicate n c' ++ s
We need to apply flip
to the result 32 of applying use5
to it's first three arguments,
so 31 that's the result of the result of the result:
use5' = (result.result.result) flip use5
Why 30 not save thinking later and define
swap_1_2 :: (a1 -> a2 -> other) -> (a2 -> a1 -> other)
swap_2_3 :: (a1 -> a2 -> a3 -> other) -> (a1 -> a3 -> a2 -> other)
--skip a few type signatures and daydream about scrap-your-boilerplate and Template Haskell
swap_1_2 = flip
swap_2_3 = result flip
swap_3_4 = (result.result) flip
swap_4_5 = (result.result.result) flip
swap_5_6 = (result.result.result.result) flip
...and 29 that's where you should stop if you like 28 simplicity and elegance.
Note that the 27 type other
could be b -> c -> d
so because of fabulous Curry 26 and right associativity of ->
,
swap_2_3 works 25 for a function which takes any number of 24 arguments above two.
For anything more complicated, you 23 should really write a permuted function 22 by hand.
What follows is just for the sake 21 of intellectual curiosity.
Now, what about 20 swapping the second and fourth arguments? [Aside: there's 19 a theorem I remember from my algebra lectures 18 that any permutation can be made as the 17 composition of swapping adjacent items.]
We 16 could do it like this:
step 1: move 2 next 15 to 4 (swap_2_3
)
a1 -> a2 -> a3 -> a4 -> otherstuff
a1 -> a3 -> a2 -> a4 -> otherstuff
swap them there using swap_3_4
a1 -> a3 -> a2 -> a4 -> otherstuff
a1 -> a3 -> a4 -> a2 -> otherstuff
then swap 4 14 back to position 2 using swap_2_3
again:
a1 -> a3 -> a4 -> a2 -> otherstuff
a1 -> a4 -> a3 -> a2 -> otherstuff
so
swap_2_4 = swap_2_3.swap_3_4.swap_2_3
Maybe 13 there's a more terse way of getting there 12 directly with lots of results and flips 11 but random messing didn't find it for me!
Similarly, to 10 swap 1 and 5 we can move 1 over to 4, swap 9 with 5, move 5 back from 4 to 1.
swap_1_5 = swap_1_2.swap_2_3.swap_3_4 . swap_4_5 . swap_3_4.swap_2_3.swap_1_2
Or if you 8 prefer you could reuse swap_2_4
by flipping at the 7 ends
(swapping 1 with 2 and 5 with 4), swap_2_4 6 then flipping at the ends again.
swap_1_5' = swap_1_2.swap_4_5. swap_2_4 .swap_4_5.swap_1_2
Of course 5 it's much easier to define
swap_1_5'' f a b c d e = f e b c d a
which has the 4 benefit of being clear, consise, efficient 3 and has a helpful type signature in ghci 2 without explicitly annotating it.
However, this 1 was a fantastically entertaining question, thanks.
The best way in general is to just do it 5 manually. Assume you have a function
f :: Arg1 -> Arg2 -> Arg3 -> Arg4 -> Res
and 4 you would like
g :: Arg4 -> Arg1 -> Arg3 -> Arg2 -> Res
then you write
g x4 x1 x3 x2 = f x1 x2 x3 x4
If you need 3 a particular permutation several times, then 2 you can of course abstract from it, like 1 flip
does for the two-argument case:
myflip :: (a4 -> a1 -> a3 -> a2 -> r) -> a1 -> a2 -> a3 -> a4 -> r
myflip f x4 x1 x3 x2 = f x1 x2 x3 x4
More Related questions
We use cookies to improve the performance of the site. By staying on our site, you agree to the terms of use of cookies.